UPAYA MENINGKATKAN PEMAHAMAN KONSEP IPA MATERI FOTOSINTESIS MELALUI PENERAPAN METODE EKSPERIMEN PADA SISWA SEKOLAH DASAR - Bardilah, Rahmalia Intan (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
ABSTRACT This study aims to analyze the effect of the experimental method on the understanding of science concepts of fourthgrade elementary school students. The type of research carried out uses Classroom Action Research with Kurt Lewin's model procedures. The population of this study is 21 fourth-grade students. Data on the ability to understand science concepts was collected using essay-shaped questions. The data obtained were then explained using descriptive and inferential statistical analysis techniques (t-test). Based on the calculation, data obtained showed an increase in the cycle, but in cycles I to II there was no increase due to obstacles, with the results being Cycle I: 42.85%, cycle II: 42.85% and cycle III: 85.71%. This means that there is an increase in each cycle in the results of the acquisition of conceptual understanding abilities. So, it can be concluded that there is a significant effect of the application of the experimental method on the understanding of science concepts of fourthgrade elementary school students. The implication of the application of the experimental method is that students become active in participating in learning activities. The application of the experimental method that refers to problems makes students practice in understanding a concept. Keywords: Education, conceptual understanding, experimental method